Variation in the P2-S2 stereochemical selectivity towards the enantiomeric N-acetylphenylalanylglycine 4-nitroanilides among the cysteine proteinases papain, ficin and actinidin. - Patel, M (1992)
1. Values of the kinetic specificity constant, kcat./Km, for the hydrolysis of N-acetyl-L-phenylalanylglycine 4-nitroanilide (I) and of its D-enantiomer (II) catalysed by ficin (EC 3.4.22.3) and by actinidin (EC 3.4.22.14) at pH 6.0, I 0.1 mol/l, 8.3% (v/v) NN-dimethylformamide and 25 degrees C were determined by using initial-rate data with [S] much less than Km and weighted nonlinear regression analysis as: for ficin, (kcat./Km)L = 271 +/- 6 M-1.s-1, (kcat./Km)D = 2.9 +/- 0.1 M-1.s-1, and for actinidin (kcat./Km)L = 13.3 +/- 0.7 M-1.s-1, (kcat/Km)D = 0.34 +/- 0.01 M-1.s-1.2. These data and analogous values for the corresponding reactions catalysed by papain (EC 3.4.22.2), (kcat./Km)L = 2064 +/- 31 M-1.s-1, (kcat./Km)D = 5.5 +/- 0.1 M-1.s-1, demonstrate marked variation in stereochemical selectivity for substrates (I) and (II) among the three cysteine proteinases with the following values for the index of stereochemical selectivity Iss = (kcat./Km)L/(kcat./Km)D: for papain, 375; for ficin 93; for actinidin 39. 3. Model building suggests ways in which, for the papain-catalysed reactions, binding interactions involving the extended acyl groups of the substrates may need to change as the reaction proceeds from adsorptive complex (ES) to tetrahedral intermediate (THI) before its rate-determining, general acid-catalysed collapse to acylenzyme intermediate. In particular, satisfactory alignment in the catalytic site at the THI stage of the acylation process appears to demand rotation of the substrate moiety about its long axis. 4. The different consequences of this rotation for the L- and D-enantiomers suggest that for closely related systems the greater the extent of this rotational adjustment the greater would be the value of Iss.5. For the actinidin-substrate combinations, model building suggests that even at the ES complex stage of catalysis it is not possible to approach optimized P2-S2 contacts and the three hydrogen-bonding interactions deduced for papain-ligand complexes in the absence of significant movement of protein conformation. Possible binding modes in which some of the interactions deduced for papain are relaxed are discussed. Consideration of postulated binding modes in the various transition states is shown to account for the order of reactivity reflected in values kcat./Km for the four reactions involving papain (Pap) and actinidin (Act) with the L- and D-enantiomeric substrates: Pap-L much greater than Act-L greater than Pap-D much greater than Act-D.(ABSTRACT TRUNCATED AT 400 WORDS)